A dry electrode binder, its preparation method and application
Patent Information
- Application Number
- CN202111667044.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-12-31
AI Technical Summary
[0003]CN113223860A公开了一种干式储能装置电极及其制造方法,其中复合粘合剂材料包含PTFE、聚偏二氟乙烯、聚偏二氟乙烯共聚物或聚环氧乙烷中的至少一种,采用喷射研磨等方式使PTFE经过高剪切过程发生原位纤维化,添加其他粘合剂缓解了单一PTFE作为电极粘合剂时不稳定的情况,但是无法避免高温高剪切的苛刻条件
[0076]本发明提供了一种具有核壳结构的干电极粘结剂,为丙烯酸酯类及其共聚物的粘结剂体系,粘结剂强,在干电极制备过程中混料条件温和,克服了应用PTFE的干电极制备过程中需要在高压高剪切的配料罐里进行混料的缺点。
Smart Images

Figure CN116410407B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode material technology, specifically relating to a dry electrode binder, its preparation method, and its application. Background Technology
[0002] Currently, the commercially available products using dry electrode technology are supercapacitors, while there are no commercially available lithium-ion batteries using this technology. This is partly because the binder system for dry electrodes is not yet fully suitable for lithium-ion battery systems. Currently, the mature binder used in the dry electrode field is polytetrafluoroethylene (PTFE), which utilizes its ability to undergo in-situ fibrosis under high pressure and high shear to achieve bonding of the active material. However, the preparation of dry electrodes requires mixing in a high-pressure, high-shear mixing tank and high-pressure extrusion coating onto the current collector.
[0003] CN113223860A discloses an electrode for a dry energy storage device and its manufacturing method. The composite binder material includes at least one of PTFE, polyvinylidene fluoride, polyvinylidene fluoride copolymer, or polyethylene oxide. The PTFE is subjected to in-situ fiberization through a high-shear process by methods such as jet milling. The addition of other binders alleviates the instability of PTFE as a single electrode binder, but it cannot avoid the harsh conditions of high temperature and high shear.
[0004] Therefore, in this field, it is desirable to develop a non-PTFE dry electrode binder system to overcome the disadvantage that mixing is required in a high-pressure, high-shear mixing tank during the preparation of PTFE dry electrodes. Summary of the Invention
[0005] The purpose of this invention is to provide a dry electrode binder, its preparation method, and its application. The dry electrode binder has a core-shell structure and is a binder system based on acrylates and their copolymers. It exhibits strong binding properties and provides mild mixing conditions during dry electrode preparation, overcoming the disadvantage of requiring mixing in a high-pressure, high-shear mixing tank during the preparation of PTFE-based dry electrodes.
[0006] To achieve this objective, the present invention employs the following technical solution:
[0007] In a first aspect, the present invention provides a dry electrode adhesive having a core-shell structure, the core-shell structure having an outermost shell layer and a core layer located inside the shell layer, the core layer being a first polymer layer comprising any one or a combination of at least two of acrylate monomers, acrylamide monomers, or acrylonitrile monomers, and the shell layer being a second polymer layer comprising styrene monomers and acrylate monomers.
[0008] In this invention, the polymer monomers of the first polymer layer include any one or a combination of at least two of acrylate monomers, acrylamide monomers, or acrylonitrile monomers.
[0009] In this invention, the polymer monomers of the second polymer layer include styrene monomers and acrylate monomers.
[0010] In this invention, the core layer is a first polymer layer obtained by polymerizing any one or at least two of acrylate monomers, acrylamide monomers, or acrylonitrile monomers. Specifically, the first polymer can be a homopolymer or copolymer of acrylate monomers, a homopolymer or copolymer of acrylamide monomers, a homopolymer of acrylonitrile monomers, a copolymer of acrylate monomers and acrylamide monomers, a copolymer of acrylate monomers and acrylonitrile monomers, a copolymer of acrylamide monomers and acrylonitrile monomers, or a copolymer of acrylate monomers, acrylamide monomers, and acrylonitrile monomers. The shell layer is a copolymer of styrene monomers and acrylate monomers.
[0011] This invention provides a dry electrode adhesive with a core-shell structure. The acrylate monomers in the core layer can adjust the Tg and adhesion of the adhesive, while the acrylamide and acrylonitrile monomers can improve the cohesive strength and ionic conductivity of the adhesive. The styrene monomers in the shell layer can adjust the Tg of the adhesive, making it a high-Tg component, and can also improve the ionic conductivity of the adhesive. The acrylate monomers in the shell layer mainly provide adhesion.
[0012] Preferably, the particle size of the dry electrode binder is 200nm-10μm, for example, it can be 200nm, 400nm, 500nm, 800nm, 1μm, 3μm, 5μm, 8μm or 10μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0013] Preferably, the weight ratio of the polymers in the core layer and the shell layer is (10-2):1, for example, it can be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, or 2:1.
[0014] In this invention, by ensuring that the weight ratio of the polymers in the core layer and the shell layer is within the specified range, it is possible to control the core layer and the shell layer of the particles in the binder emulsion to have appropriate thickness and appropriate weight ratio. At the same time, the glass transition temperature Tg of the core layer and the shell layer are adjusted respectively, so as to provide a certain ionic conductivity while ensuring the adhesive force.
[0015] Preferably, the thickness of the core layer is 190nm-9μm, for example 190nm, 200nm, 250nm, 280nm, 300nm, 500nm, 800nm, 1μm, 3μm, 5μm, 8μm or 9μm.
[0016] Preferably, the thickness of the shell layer is 10nm-1μm, such as 10nm, 20nm, 40nm, 80nm, 100nm, 300nm, 500nm, 800nm or 1μm.
[0017] Preferably, the glass transition temperature (Tg) of the core layer is in the range of -30 to 30°C, for example, it can be -30°C, -20°C, -10°C, -5°C, 0°C, 10°C, 20°C or 30°C, and the glass transition temperature (Tg) of the shell layer is in the range of -10 to 60°C, for example, it can be -10°C, -5°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C or 60°C.
[0018] In this invention, based on the monomer components added to the core and shell layers and differential scanning calorimetry (DSC) testing, the core layer has a lower glass transition temperature (Tg) with a range of -30 to 30°C, while the shell layer has a higher glass transition temperature (Tg) with a range of -10 to 60°C.
[0019] Preferably, the acrylate monomers include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate. For example, it can be methyl acrylate and ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, or isoamyl acrylate, but is not limited to the listed types. Other unlisted types within the scope of acrylate monomers are also applicable.
[0020] Preferably, the acrylamide monomer includes any one or a combination of at least two of methacrylamide, N-hydroxymethylacrylamide, or N,N-dimethylacrylamide. For example, it can be methacrylamide and N-hydroxymethylacrylamide, methacrylamide, or N,N-dimethylacrylamide, but is not limited to the listed types. Other unlisted types within the acrylamide monomer range are also applicable.
[0021] In a second aspect, the present invention provides a method for preparing the dry electrode binder described in the first aspect, the method comprising the following steps:
[0022] (1) Add a first polymerizing monomer and an initiator to an aqueous solution containing an emulsifier and / or a dispersant to carry out a first polymerization reaction to obtain a primary emulsion, wherein the first polymerizing monomer includes any one or a combination of at least two of acrylate monomers, acrylamide monomers or acrylonitrile monomers.
[0023] (2) Add a second polymerizing monomer and an initiator to the primary emulsion obtained in step (1) to carry out a second polymerization reaction to obtain a binder emulsion. The second polymerizing monomer includes styrene monomer and acrylate monomer.
[0024] In this invention, the polymerization method of the binder is emulsion polymerization or microemulsion polymerization to obtain binder polymer particles.
[0025] Preferably, after the second polymerization reaction in step (2), the method further includes a step of removing unreacted monomers; that is, the method includes the following steps:
[0026] (1) Add a first polymerizing monomer and an initiator to an aqueous solution containing an emulsifier and a dispersant, and carry out a first polymerization reaction to obtain a primary emulsion. The first polymerizing monomer includes any one or a combination of at least two of acrylate monomers, acrylamide monomers or acrylonitrile monomers.
[0027] (2) Add a second polymerizing monomer and an initiator to the primary emulsion obtained in step (1) to carry out a second polymerization reaction, remove unreacted monomers, and obtain a binder emulsion. The second polymerizing monomer includes styrene monomer and acrylate monomer.
[0028] Preferably, the weight ratio of the first polymeric monomer to the second polymeric monomer is (10-2):1, for example, it can be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, or 2:1.
[0029] In this invention, by ensuring that the weight ratio of the first polymeric monomer in step (1) to the second polymeric monomer in step (2) is within the specified range, it is possible to control the core and shell layers of the particles in the binder emulsion to have appropriate thicknesses and appropriate weight ratios. At the same time, the glass transition temperatures Tg of the core and shell layers are adjusted respectively, thereby providing a certain ionic conductivity while ensuring the adhesive force.
[0030] Preferably, based on the total weight of the emulsifier, dispersant, first polymerizing monomer, and initiator described in step (1) as 100%, the total proportion of the dispersant and emulsifier is 0.1%-10%, the proportion of the first polymerizing monomer is 80%-99.8%, and the proportion of the initiator is 0.1%-10%.
[0031] In this invention, taking the total weight of the emulsifier, dispersant, first polymerizing monomer, and initiator described in step (1) as 100%, the total proportion of the dispersant and emulsifier is 0.1%-10%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0032] In this invention, taking the total weight of the emulsifier, dispersant, first polymerizing monomer, and initiator described in step (1) as 100%, the proportion of the first polymerizing monomer is 80%-99.8%, for example, it can be 80%, 83%, 85%, 88%, 90%, 92%, 95%, 98%, or 99.8%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0033] In this invention, the proportion of the initiator is 0.1%-10%, based on the total weight of the emulsifier, dispersant, first polymerizing monomer and initiator described in step (1) as 100%. For example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0034] Preferably, the total weight ratio of the emulsifier, dispersant, first polymerizing monomer, and initiator in the primary emulsion is 2%-20%, for example, it can be 2%, 5%, 8%, 10%, 13%, 15%, 18%, or 20%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0035] Preferably, the emulsifier in step (1) is any one or a combination of at least two of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or sodium dodecyl sulfonate.
[0036] Preferably, the dispersant in step (1) is any one or a combination of at least two of polyvinyl alcohol, polyvinylpyrrolidone, tetradecane, hexadecane or octadecane.
[0037] Preferably, the initiator in step (1) includes an azo initiator, a peroxide initiator, or a redox initiator.
[0038] Preferably, the azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0039] Preferably, the peroxide initiator is benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, or potassium persulfate.
[0040] Preferably, the redox initiator is ammonium persulfate and sodium sulfite, or ammonium persulfate and sodium bisulfite.
[0041] Preferably, the temperature of the first polymerization reaction in step (1) is 60-95℃, for example, it can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, or 95℃.
[0042] Preferably, the time for the first polymerization reaction in step (1) is 3-10 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0043] Preferably, the acrylate monomers include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate. For example, it can be methyl acrylate and ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, or isoamyl acrylate, but is not limited to the listed types. Other unlisted types within the scope of acrylate monomers are also applicable.
[0044] Preferably, the acrylamide monomer includes any one or a combination of at least two of methacrylamide, N-hydroxymethylacrylamide, or N,N-dimethylacrylamide. For example, it can be methacrylamide and N-hydroxymethylacrylamide, methacrylamide, or N,N-dimethylacrylamide, but is not limited to the listed types. Other unlisted types within the acrylamide monomer range are also applicable.
[0045] Preferably, based on the total weight of the second polymerizing monomer and the initiator in step (2) being 100%, the proportion of the initiator is 0.1%-5%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0046] Preferably, based on the total weight of the second polymerizing monomer and the initiator in step (2) as 100%, the weight percentage of styrene monomer in the second polymerizing monomer in step (2) is 1%-40%, and the weight percentage of acrylate monomer is 55%-98.9%.
[0047] In this invention, the weight percentage of styrene monomer in the second polymer monomer in step (2) is 1%-40%, for example, it can be 1%, 2%, 5%, 8%, 10%, 15%, 18%, 20%, 25%, 30%, 35% or 40%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0048] In this invention, the weight percentage of acrylate monomers in the second polymerizing monomer in step (2) is 55%-98.9%, for example, it can be 55%, 58%, 60%, 65%, 70%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 92%, 95%, 98%, or 98.9%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0049] In this invention, by controlling the feeding ratio and calculating the weight of the monomers added to each layer, the shell thickness is 10nm-1μm, the core thickness is 190nm-9μm, the shell has a thinner structure, the core has a thicker thickness, and the preferred weight ratio between the core and shell is (10-2):1.
[0050] Preferably, the initiator in step (2) includes an azo initiator, a peroxide initiator, or a redox initiator.
[0051] Preferably, the azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0052] Preferably, the peroxide initiator is benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, or potassium persulfate.
[0053] Preferably, the redox initiator is ammonium persulfate and sodium sulfite, or ammonium persulfate and sodium bisulfite.
[0054] Preferably, the temperature of the second polymerization reaction in step (2) is 60-90℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, or 90℃.
[0055] Preferably, the time for the second polymerization reaction in step (2) is 2-8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours.
[0056] Preferably, the first polymer reaction in step (1) and the second polymer reaction in step (2) are carried out under nitrogen protection.
[0057] Preferably, the acrylate monomers include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate. For example, it can be methyl acrylate and ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, or isoamyl acrylate, but is not limited to the listed types. Other unlisted types within the scope of acrylate monomers are also applicable.
[0058] Thirdly, the present invention provides a negative electrode dry powder mixture, the negative electrode dry powder mixture comprising the dry electrode binder, negative electrode active material, and conductive agent as described in the first aspect. Compared with traditional wet slurry, the dry powder mixture used to prepare dry electrodes has significant advantages in terms of storage stability and ease of transportation.
[0059] Preferably, the negative electrode active material includes a carbon active material.
[0060] Preferably, the carbon-active material is graphite.
[0061] Preferably, the conductive agent includes acetylene black or carbon black.
[0062] Preferably, the negative electrode dry powder mixture contains 0.5-10 wt% (e.g., 0.5 wt%, 1 wt%, 3 wt%, 5 wt%, 8 wt% or 10 wt%) of dry electrode binder.
[0063] Preferably, the negative electrode dry powder mixture contains 85-96 wt% (e.g., 85 wt%, 88 wt%, 90 wt%, 93 wt%, or 96 wt%) of negative electrode active material.
[0064] Preferably, the negative electrode dry powder mixture contains 0.5-5 wt% (e.g., 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt%) of a conductive agent.
[0065] Preferably, the negative electrode dry powder mixture is obtained by wet mixing of dry electrode binder, negative electrode active material and conductive agent, and then removing the solvent water.
[0066] In this invention, the solvent removal methods include vacuum drying, centrifugation, or freeze drying.
[0067] Fourthly, the present invention provides a dry electrode negative electrode, the dry electrode negative electrode comprising the negative electrode dry powder mixture as described in the third aspect.
[0068] Preferably, the dry electrode negative electrode is obtained by hot rolling the negative electrode dry powder mixture into a self-supporting film or by directly hot rolling it onto the current collector.
[0069] In this invention, the hot rolling temperature range is 30-120℃, for example, it can be 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃.
[0070] The hot rolling process can be performed more than once to achieve a specific electrode thickness and good adhesion to the current collector.
[0071] The present invention adopts a dry electrode technology route of wet mixing followed by dry coating. The wet mixing process utilizes the advantages of wet methods, which enables the dry electrode binder, negative electrode active material and conductive agent to be uniformly mixed under relatively mild conditions, without the need for harsh conditions of high pressure and high shear.
[0072] The core-shell structured binder of this invention is suitable for the dry electrode negative electrode process route of wet mixing followed by dry coating. The binder shell layer can maintain the binder particles in a good spherical shape, and can improve the dispersion ability of the negative electrode dry powder mixture in the wet mixing process. The binder core layer mainly provides the bonding force. In the subsequent dry electrode dry coating process, the binder particles undergo a certain degree of deformation through hot rolling, changing from a spherical structure to a non-spherical structure. The binder core layer material is exposed, thereby providing a larger bonding area between it and the active material, which is conducive to achieving higher bonding force.
[0073] Fifthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a dry electrode negative electrode as described in the fourth aspect.
[0074] The dry electrode binder of the present invention has a core-shell structure and is a binder system of acrylates and their copolymers. It adopts a dry electrode process route of wet mixing followed by dry coating. This can not only take advantage of the mixing uniformity of wet mixing to overcome the process difficulty of dry mixing, but also maintain the technical characteristics of dry electrodes. This achieves a breakthrough in the existing dry electrode production process, thereby enabling dry electrode technology to be better applied in the field of lithium-ion batteries.
[0075] Compared with the prior art, the present invention has the following beneficial effects:
[0076] This invention provides a core-shell structured dry electrode binder, which is an acrylate and its copolymer binder system. The binder is strong and the mixing conditions during the dry electrode preparation process are mild, overcoming the disadvantage of needing to mix in a high-pressure, high-shear mixing tank during the preparation of PTFE-based dry electrodes.
[0077] The binder shell layer enables the binder particles to maintain a good spherical shape, which can improve the dispersion ability of the negative electrode dry powder mixture in the wet mixing process. The binder core layer mainly provides the bonding force. In the subsequent dry electrode dry coating process, the binder particles undergo a certain degree of deformation through hot rolling, changing from a spherical structure to a non-spherical structure. The binder core layer material is exposed, which can provide a larger bonding area and help achieve higher bonding force. Attached Figure Description
[0078] Figure 1 The image shows a scanning electron microscope (SEM) image of the negative electrode dry powder mixture prepared in Example 1, with a scale bar of 1 μm.
[0079] Figure 2 Cycle performance graphs of lithium-ion coin cells prepared in Application Example 1 and Comparative Application Example 6. Detailed Implementation
[0080] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be considered as specific limitations thereof.
[0081] Example 1
[0082] In this embodiment, a dry electrode binder and its preparation method are provided, the preparation method comprising the following steps:
[0083] (1) Place 800g of an aqueous solution containing 5g of polyvinyl alcohol (PVA) in a 2000L reactor. Under stirring at 250rpm, introduce nitrogen gas with a purity of ≥99.9%, add the first polymerization monomer, including 100g of methyl acrylate, 10g of methacrylamide and 10g of acrylonitrile, add 0.5g of initiator azobisisobutyronitrile (AIBN), continue stirring and continuously introduce nitrogen gas, raise the temperature of the solution to 75℃, and carry out the first polymerization reaction for 5h to obtain the primary emulsion;
[0084] (2) Add the second polymerization monomer, including 20g of butyl acrylate and 10g of styrene monomer, to the primary emulsion in step (1), add 0.2g of initiator AIBN, continuously introduce nitrogen gas, maintain the solution temperature at 75°C, and continuously stir to carry out the second polymerization reaction for 5h. Reduce the pressure of the polymerization product to a vacuum degree below 0.1MPa using a vacuum pump to remove the residual unreacted monomer components and obtain the dry electrode binder.
[0085] The dry electrode binder has a core-shell structure, which has an outermost shell layer and a core layer inside the shell layer. The core layer is a first polymer layer, which includes methyl acrylate monomer, methacrylamide monomer, and acrylonitrile monomer. The shell layer is a second polymer layer, which includes styrene monomer and butyl acrylate monomer.
[0086] Example 2
[0087] In this embodiment, a dry electrode binder and its preparation method are provided, the preparation method comprising the following steps:
[0088] (1) Place 800g of an aqueous solution containing 1g sodium dodecyl sulfate and 2g polyvinylpyrrolidone in a 2000L reactor. Under stirring at 250rpm, introduce nitrogen gas with a purity ≥99.9%, add the first polymerization monomer, including 100g of n-amyl acrylate and 10g of N-hydroxymethylacrylamide, add 3g of initiator azobisisobutyronitrile (AIBN), continue stirring, continue introducing nitrogen gas, heat the solution to 65℃, and carry out the first polymerization reaction for 8h to obtain the primary emulsion;
[0089] (2) Add the second polymerization monomer, including 42.6g of butyl methacrylate and 11g of styrene monomer, to the primary emulsion in step (1), add 1.4g of initiator AIBN, continuously introduce nitrogen gas, maintain the solution temperature at 65°C, and continuously stir to carry out the second polymerization reaction for 6 hours. Reduce the pressure of the polymerization product to a vacuum degree below 0.1MPa using a vacuum pump to remove the residual unreacted monomer components and obtain the dry electrode binder.
[0090] The dry electrode binder has a core-shell structure, which has an outermost shell layer and a core layer inside the shell layer. The core layer is a first polymer layer, which includes n-amyl acrylate monomer and N-hydroxymethylacrylamide monomer. The shell layer is a second polymer layer, which includes styrene monomer and butyl methacrylate monomer.
[0091] Example 3
[0092] In this embodiment, a dry electrode binder and its preparation method are provided, the preparation method comprising the following steps:
[0093] (1) Place 800g of an aqueous solution containing 5g of polyvinyl alcohol (PVA) in a 2000L reactor. Under stirring at 250rpm, introduce nitrogen gas with a purity of ≥99.9%, add the first polymerization monomer, including 100g of methyl methacrylate, 10g of N,N-dimethylacrylamide and 3g of acrylonitrile, add 0.5g of initiator azobisisobutyronitrile (AIBN), continue stirring and continuously introduce nitrogen gas, raise the temperature of the solution to 85℃, and carry out the first polymerization reaction for 5h to obtain the primary emulsion;
[0094] (2) Add the second polymerization monomer, including 20g of hydroxypropyl acrylate and 10g of styrene monomer, to the primary emulsion in step (1), add 1g of initiator AIBN, continuously introduce nitrogen gas, maintain the solution temperature at 80°C, and continuously stir to carry out the second polymerization reaction for 4 hours. Reduce the pressure of the polymerization product to a vacuum degree below 0.1MPa using a vacuum pump to remove the residual unreacted monomer components and obtain the dry electrode binder.
[0095] The dry electrode binder has a core-shell structure, which has an outermost shell layer and a core layer inside the shell layer. The core layer is a first polymer layer, which includes methyl methacrylate monomer, N,N-dimethylacrylamide and acrylonitrile monomer. The shell layer is a second polymer layer, which includes styrene monomer and hydroxypropyl acrylate monomer.
[0096] Example 4
[0097] In this embodiment, a dry electrode binder and its preparation method are provided, the preparation method comprising the following steps:
[0098] (1) Place 800g of an aqueous solution containing 0.16g of polyvinyl alcohol (PVA) in a 2000L reactor. While stirring at 250rpm, introduce nitrogen gas with a purity of ≥99.9%, add the first polymerization monomer, including 120g of methyl acrylate, 30g of methacrylamide and 9g of acrylonitrile, and add 0.16g of benzoyl peroxide initiator. Continue stirring and introducing nitrogen gas, raise the temperature of the solution to 60℃, and carry out the first polymerization reaction for 10h to obtain the primary emulsion.
[0099] (2) Add the second polymerization monomer, including 12g of butyl acrylate and 8g of styrene monomer, to the primary emulsion in step (1), add 1.05g of initiator AIBN, continuously introduce nitrogen gas, maintain the solution temperature at 60°C, and continuously stir to carry out the second polymerization reaction for 8 hours. Reduce the pressure of the polymerization product to a vacuum degree below 0.1MPa using a vacuum pump to remove the residual unreacted monomer components and obtain the dry electrode binder.
[0100] The dry electrode binder has a core-shell structure, which has an outermost shell layer and a core layer inside the shell layer. The core layer is a first polymer layer, which includes methyl acrylate monomer, methacrylamide monomer, and acrylonitrile monomer. The shell layer is a second polymer layer, which includes styrene monomer and butyl acrylate monomer.
[0101] Example 5
[0102] In this embodiment, a dry electrode binder and its preparation method are provided, the preparation method comprising the following steps:
[0103] (1) Place 800g of an aqueous solution containing 4g of polyvinyl alcohol (PVA) in a 2000L reactor. Under stirring at 250rpm, introduce nitrogen gas with a purity of ≥99.9%, add the first polymerization monomer, including 70g of methyl acrylate, 5g of methacrylamide and 5g of acrylonitrile, add 4g of ammonium persulfate as initiator, continue stirring and continuously introduce nitrogen gas, heat the solution to 95℃, and carry out the first polymerization reaction for 3h to obtain the primary emulsion;
[0104] (2) Add the second polymerization monomer, including 30.4g of butyl acrylate and 9.6g of styrene monomer, to the primary emulsion in step (1), add 0.04g of initiator AIBN, continuously introduce nitrogen gas, maintain the solution temperature at 90°C, and continuously stir to carry out the second polymerization reaction for 2 hours. Reduce the pressure of the polymerization product to a vacuum degree below 0.1MPa using a vacuum pump to remove the residual unreacted monomer components and obtain the dry electrode binder.
[0105] The dry electrode binder has a core-shell structure, which has an outermost shell layer and a core layer inside the shell layer. The core layer is a first polymer layer, which includes methyl acrylate monomer, methacrylamide monomer, and acrylonitrile monomer. The shell layer is a second polymer layer, which includes styrene monomer and butyl acrylate monomer.
[0106] Example 6
[0107] The difference between this embodiment and Example 1 is that the first polymerizing monomer in step (1) is 120g of methyl acrylate, while the rest is the same as in Example 1.
[0108] Example 7
[0109] The difference between this embodiment and Example 1 is that the first polymerizing monomer in step (1) is 120g of methacrylamide, while the rest is the same as in Example 1.
[0110] Example 8
[0111] The difference between this embodiment and embodiment 1 is that the first polymerizing monomer in step (1) is 120g of acrylonitrile, while the rest is the same as in embodiment 1.
[0112] Example 9
[0113] The difference between this embodiment and Embodiment 1 is that the first polymerizing monomer in step (1) includes 110g of methyl acrylate and 10g of acrylonitrile, while the rest are the same as in Embodiment 1.
[0114] Example 10
[0115] The difference between this embodiment and Example 1 is that the first polymerizing monomer in step (1) includes 110g of methacrylamide and 10g of acrylonitrile, while the rest are the same as in Example 1.
[0116] Example 11
[0117] The difference between this embodiment and Example 1 is that the first polymerizing monomer in step (1) includes 100g of methyl acrylate and 20g of methacrylamide, while the rest is the same as in Example 1.
[0118] Comparative Example 1
[0119] The only difference between Comparative Example 1 and Example 1 is that the preparation method only carried out the first polymerization reaction in step (1) to obtain the adhesive product.
[0120] Comparative Example 2
[0121] The only difference between Comparative Example 1 and Example 1 is that the preparation method only carried out the second polymerization reaction in step (2) to obtain the adhesive product.
[0122] Comparative Example 3
[0123] The only difference between Comparative Example 1 and Example 1 is that the first polymerization reaction time in step (1) of the preparation method is 2.5 h, and the second polymerization reaction time in step (2) is 2 h, to obtain the adhesive product.
[0124] Comparative Example 4
[0125] The only difference between this comparative example and Example 1 is that the weight ratio of the first polymeric monomer in step (1) to the second polymeric monomer in step (2) of the preparation method is 1:1.
[0126] Comparative Example 5
[0127] The only difference between this comparative example and Example 1 is that the weight ratio of the first polymeric monomer in step (1) to the second polymeric monomer in step (2) of the preparation method is 15:1.
[0128] Application Example 1-11 and Comparative Application Example 1-5
[0129] The preparation process of the negative electrode dry powder mixture is as follows:
[0130] Artificial graphite (anode active material), superconducting carbon black (Surper P), and the dry electrode binder prepared in Examples 1-11 and Comparative Examples 1-5 were mixed in a wet process at a mass ratio of 96:1:3. Deionized water was added to prepare a negative electrode slurry with a solid content of 40%. The slurry was dispersed in a disperser at 800 rpm for 30 s and then at 2000 rpm for 10 min to ensure uniform dispersion. The dispersed negative electrode slurry was then vacuum dried at room temperature to remove solvent moisture, resulting in the negative electrode dry powder mixture prepared in Examples 1-11 and Comparative Examples 1-5.
[0131] The preparation process of the dry electrode is as follows:
[0132] Artificial graphite (negative electrode active material), superimposed carbon black (Surper P), and the dry electrode binder prepared in Examples 1-11 and Comparative Examples 1-5 were wet-mixed at a mass ratio of 96:1:3. Deionized water was added to prepare a negative electrode slurry with a solid content of 40%. The slurry was dispersed using a disperser at 800 rpm for 30 s and then at 2000 rpm for 10 min to ensure uniform dispersion. The dispersed negative electrode slurry was then vacuum-dried at room temperature to remove solvent moisture, resulting in a negative electrode dry powder mixture. This mixture was then dry-coated onto a current collector copper foil and hot-rolled at 40°C to obtain the dry electrode negative electrode sheets of Application Examples 1-10 and Comparative Application Examples 1-5.
[0133] Comparative Application Example 6
[0134] The only difference between this comparative application example and application example 1 is that the dispersed negative electrode slurry is directly coated onto the current collector copper foil and hot-rolled at 40°C to obtain the conventional wet electrode negative electrode sheet of comparative application example 6.
[0135] The negative electrode dry powder mixture prepared in Example 1 was characterized using a scanning electron microscope (ZEISS, GeminiSEM 500), and the results are as follows: Figure 1 As shown, from Figure 1 As can be seen, the particle size of the negative electrode dry powder mixture is 1 μm, and the dry electrode binder particles are adsorbed on the surface of the graphite particles.
[0136] The preparation method of lithium-ion batteries is as follows:
[0137] The dry electrode negative electrode sheets of Application Examples 1-10, the dry electrode negative electrode sheets of Comparative Application Examples 1-5, and the conventional wet electrode negative electrode sheet of Comparative Application Example 6 were assembled with lithium metal electrodes to form lithium-ion coin cells. LiPF6 was dissolved at a concentration of 1 mol / L in an electrolyte with a volume ratio of EC / DEC / EMC = 2:3:1. After the coin cell assembly was completed, the capacity first-efficiency and cycle tests were performed according to the following steps: standing for 2 hours; constant current discharge: 0.1C to 0.005V; 0.08C to 0.001V; 0.05C to 0.001V; 0.02C to 0.001V; standing for 10 minutes; constant current charging: 0.1C to 1.5V.
[0138] Figure 2 The cycling performance diagrams of the lithium-ion coin cells prepared in Application Example 1 and Comparative Application Example 6 are shown below. Figure 2 It can be seen that the dry electrode negative electrode prepared by the wet mixing and dry coating process of the present invention has a higher capacity retention rate than the traditional wet electrode negative electrode, thereby improving the cycle performance of lithium-ion batteries.
[0139] The test results for capacity and initial coulombic efficiency are shown in Table 1.
[0140] Table 1
[0141]
[0142]
[0143] The data in Table 1 demonstrates that the lithium-ion coin cells prepared in Examples 1 to 11 of this invention have a charging specific capacity of not less than 352.1 mAh / g and a discharge specific capacity of not less than 370.9 mAh / g, while the initial coulombic efficiency is as high as 94.7% or more. This indicates that the negative electrode dry powder mixture prepared using the dry electrode binder provided by this invention can achieve relatively high values in terms of capacity and initial coulombic efficiency in the coin cell test of the prepared dry electrode negative electrode sheet.
[0144] Compared with Application Example 1, it can be seen that the capacity and initial coulombic efficiency data of the lithium-ion coin cells prepared in Comparative Application Examples 1 to 6 are somewhat different from the values of the lithium-ion coin cells provided in Application Example 1. This indicates that the dry electrode preparation process of the present invention, which involves wet mixing followed by dry coating, can achieve better electrochemical performance and give full play to the unique characteristics of dry electrodes.
[0145] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A dry electrode adhesive, characterized in that, The dry electrode binder has a core-shell structure, wherein the core-shell structure has an outermost shell layer and a core layer located inside the shell layer. The core layer is a first polymer layer, which comprises any one or a combination of at least two of acrylate monomers, acrylamide monomers, or acrylonitrile monomers. The shell layer is a second polymer layer, which is a combination of styrene monomers and acrylate monomers; The weight ratio of the polymers in the core layer to the shell layer is (10-2):1; The Tg range of the core layer is -30 to 30°C, and the Tg range of the shell layer is -10 to 60°C. The preparation method of the dry electrode binder includes the following steps: (1) Add a first polymerizing monomer and an initiator to an aqueous solution containing an emulsifier and / or a dispersant to carry out a first polymerization reaction to obtain a primary emulsion, wherein the first polymerizing monomer includes any one or a combination of at least two of acrylate monomers, acrylamide monomers or acrylonitrile monomers; (2) Add a second polymerizing monomer and an initiator to the primary emulsion obtained in step (1) to carry out a second polymerization reaction to obtain the dry electrode binder, wherein the second polymerizing monomer is a styrene monomer and an acrylate monomer; In step (1), the time for the first polymerization reaction is 3-10 hours, and in step (2), the time for the second polymerization reaction is 2-8 hours.
2. The dry electrode adhesive according to claim 1, characterized in that, The particle size of the dry electrode binder is 200nm-10μm.
3. The dry electrode adhesive according to claim 1, characterized in that, The thickness of the core layer is 190 nm to 9 μm.
4. The dry electrode adhesive according to claim 1, characterized in that, The thickness of the shell is 10 nm to 1 μm.
5. The dry electrode binder according to any one of claims 1-4, characterized in that, The acrylate monomers include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate.
6. The dry electrode binder according to any one of claims 1-4, characterized in that, The acrylamide monomers include any one or a combination of at least two of methacrylamide, N-hydroxymethylacrylamide, or N,N-dimethylacrylamide.
7. The dry electrode adhesive according to claim 1, characterized in that, Step (2) after the second polymerization reaction also includes a step of removing unreacted monomers.
8. The dry electrode adhesive according to claim 1, characterized in that, The weight ratio of the first polymeric monomer to the second polymeric monomer is (10-2):
1.
9. The dry electrode adhesive according to claim 7 or 8, characterized in that, Based on the total weight of the emulsifier, dispersant, first polymerizing monomer and initiator described in step (1) as 100%, the total proportion of the dispersant and emulsifier is 0.1%-10%, the proportion of the first polymerizing monomer is 80%-99.8%, and the proportion of the initiator is 0.1%-10%.
10. The dry electrode binder according to claim 7 or 8, characterized in that, The total weight ratio of the emulsifier, dispersant, first polymerizing monomer, and initiator in the primary emulsion is 2%-20%.
11. The dry electrode binder according to claim 7 or 8, characterized in that, The emulsifier in step (1) is any one or a combination of at least two of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or sodium dodecyl sulfonate.
12. The dry electrode binder according to claim 7 or 8, characterized in that, The dispersant in step (1) is any one or a combination of at least two of polyvinyl alcohol, polyvinylpyrrolidone, tetradecane, hexadecane or octadecane.
13. The dry electrode binder according to claim 7 or 8, characterized in that, The initiator in step (1) includes azo initiators, peroxide initiators, or redox initiators.
14. The dry electrode binder according to claim 13, characterized in that, The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
15. The dry electrode binder according to claim 13, characterized in that, The peroxide initiator is benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, or potassium persulfate.
16. The dry electrode binder according to claim 13, characterized in that, The redox initiator is a combination of ammonium persulfate and sodium sulfite, or a combination of ammonium persulfate and sodium bisulfite.
17. The dry electrode binder according to claim 7 or 8, characterized in that, In step (1), the temperature of the first polymerization reaction is 60-95℃.
18. The dry electrode binder according to claim 7 or 8, characterized in that, The acrylate monomers in step (1) include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate.
19. The dry electrode binder according to claim 7 or 8, characterized in that, The acrylamide monomers include any one or a combination of at least two of methacrylamide, N-hydroxymethylacrylamide, or N,N-dimethylacrylamide.
20. The dry electrode binder according to claim 7 or 8, characterized in that, Based on the total weight of the second polymerizing monomer and the initiator in step (2) being 100%, the proportion of the initiator is 0.1%-5%.
21. The dry electrode binder according to claim 7 or 8, characterized in that, Taking the total weight of the second polymerizing monomer and the initiator in step (2) as 100%, the weight percentage of styrene monomer in the second polymerizing monomer in step (2) is 1%-40%, and the weight percentage of acrylate monomer is 55%-98.9%.
22. The dry electrode binder according to claim 7 or 8, characterized in that, The initiator in step (2) includes azo initiators, peroxide initiators, or redox initiators.
23. The dry electrode binder according to claim 22, characterized in that, The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
24. The dry electrode adhesive according to claim 22, characterized in that, The peroxide initiator is benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, or potassium persulfate.
25. The dry electrode adhesive according to claim 22, characterized in that, The redox initiator is a combination of ammonium persulfate and sodium sulfite, or a combination of ammonium persulfate and sodium bisulfite.
26. The dry electrode binder according to claim 7 or 8, characterized in that, In step (2), the temperature of the second polymerization reaction is 60-90℃.
27. The dry electrode binder according to claim 7 or 8, characterized in that, Step (1) the first polymerization reaction and step (2) the second polymerization reaction are carried out under nitrogen protection.
28. The dry electrode binder according to claim 7 or 8, characterized in that, The acrylate monomers in step (2) include any one or a combination of at least two of the following: methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, or 2-hydroxyethyl methacrylate.
29. A negative electrode dry powder mixture, characterized in that, The negative electrode dry powder mixture includes the dry electrode binder, negative electrode active material, and conductive agent as described in any one of claims 1-28.
30. The negative electrode dry powder mixture according to claim 29, characterized in that, The negative electrode active material includes carbon active materials.
31. The negative electrode dry powder mixture according to claim 30, characterized in that, The carbon-active material is graphite.
32. The negative electrode dry powder mixture according to claim 29, characterized in that, The negative electrode dry powder mixture is obtained by wet mixing of dry electrode binder, negative electrode active material and conductive agent, and then removing the solvent water.
33. A dry electrode negative electrode, characterized in that, The dry electrode negative electrode comprises the negative electrode dry powder mixture as described in any one of claims 29-32.
34. The dry electrode negative electrode according to claim 33, characterized in that, The dry electrode negative electrode is obtained by hot rolling the negative electrode dry powder mixture into a self-supporting film or by directly hot rolling it onto the current collector.
35. A lithium-ion battery, characterized in that, The lithium-ion battery includes a dry electrode negative electrode as described in claim 33 or 34.
Citation Information
Patent Citations
Dry energy storage device electrode and methods of making the same
CN113223860A
Preparation method of lithium ion battery cathode sheet adhesive emulsion
CN103173161A
Acrylonitrile polymer emulsion bonder and preparation method therefor
CN110183584A
Binder and diaphragm, and preparation methods thereof
CN112341961A